(untitled) (Global Journal of Medical Research, 2020)
Since bacteria grow in high temperature and high humidity, bacterial food poisoning frequently occurs from the rainy season to summer. In Japan, the number of food poisoning cases is high from June to October. Maintaining a hygienic environment in the kitchen is very important for preventing food poisoning. In particular, cutting boards on which various foods are places may cause secondary pollution. Therefore, to avoid food poisoning, this study compared the ATP value of the cutting board before and after the hygiene education using the ATP wiping test and investigated the educational effect. Before hygiene education, the inspector conducted an ATP wiping test on the cutting boards for vegetables and meat that washed before and after cooking and notified the cooks of the values. The inspector conducted hygiene education while showing the cook how to clean the cutting board. The cutting board washed with detergent and sponge, rinsed with running water for 30 seconds or more, then this process was repeated twice.